5 Practices for Orchestrating Productive Task-Based Discussions in Science - Cartier, Jennifer L. (National Council of Teachers of Mathematics, 2013)
Robust and effective classroom discussions are essential for providing students with opportunities to simultaneously engage in science practices while learning key science content. Using numerous examples and science learning tasks, the authors show how teachers can plan the lesson to encourage students to not only learn science content but employ disciplinary practices as well. This volume outlines the five practices teachers need for facilitating effective inquiry-oriented classrooms:Anticipate what students will do--what strategies they will use--in solving a problemMonitor their work as th.